Orthosiphon stamineus Benth. is an outstanding food medicine: Review of phytochemical and pharmacological activities - Kamran Ashraf; Sadia Sultan; Aishah Adam (Wolters Kluwer Medknow Publications, 2018)
Orthosiphon stamineus Benth. (Lamiaceae) is a valued medicinal plant in traditional folk medicine. Many pharmacological studies have demonstrated the ability of this plant to exhibit antimicrobial, antioxidant, hepatoprotection, antigenotoxic, antiplasmodial, cytotoxic, cardioactive, antidiabetic, anti-inflammatory activies. This review is a comprehensive summary of the presently available chemical, pharmacological investigations as well as the traditional and therapeutic uses of this plant. Important and different experimental data have been addressed along with a review of all phytochemicals identified in this plant, including flavonoids, terpenoids, and essential oils. O. stamineus has wide traditional and pharmacological uses in various pathophysiological conditions. Therefore, it is an attractive subject for further experimental and clinical investigations.